Induction motor stator resistance eztimation using PI estimator - Aizat Fahmi, A.Aziz (2009)
During the operational of induction motor, stator resistance changes continuously with the temperature of the machine and this will cause trouble to operate the machine. High temperature or too low temperature will disturb the progress of the machine. When the temperature change due to the operational of the motor, the resistance values will be affected. When the temperature is high, the resistance value will increase. The current will increase and this will damage the machine. When temperature is low, the resistance will drop. Hence, the current will drop and make the machine fail to operate. This project will verify the resistance used when there is a change of the temperature value of the induction motor. This project also will reduce the overshoot stator resistance to protect the motor from damage. PI Estimator will be used in this project using MATLAB. Calculation and block diagram will be used in this project to identify the suitable resistance value due to the temperature of the machine.